Evaluation of users' awareness and their reaction on information security - Zeki, Akram M.; Hamid, Habiba (The Institute of Electrical and Electronics Engineers, Inc., 2016)
Information security (IS) simply implies the protection and preservation of information, with its central purpose being to protect and preserve the confidentiality, integrity, and availability of information. The purpose of this research therefore was to study and evaluate users' Information Security Awareness (ISA) and perception of IS issues amongst post graduate (PG) students of a university. To this end, data collection was elicited through the administration of questionnaires and interviews. This study mixed both the quantitative and qualitative method. The quantitative data from primary source of an administered questionnaire was analyzed using the SPSS version 20. The qualitative method of an interview was recorded, played in breaks and represented on a graph and the results were compared. Findings indicated that the participants of this study were conversant with information security issues with a high degree of awareness because most of the participants have up-to-date antivirus to protect them against malware. There is no significant difference on ISA between males and females.